Education in Medicine as a component of Modern Science; restoring the balance - SN Arseculeratne (Anuradhapura Medical Journal, 2014)
Since 1871 when the Colombo Medical College was instituted, the education of undergraduates and postgraduates in medicine, over the succeeding decades, had the prime aim of producing doctors who could deliver health care. This was the continuation of British colonial policy. The establishment of the University of Ceylon in 1942 continued this orientation, while in later decades and in contemporary times, the place of medicine as a component of modern science has been ignored. If the major function of a modern university in the sciences is to establish a scientific culture, an overhaul of the system of medical education is essential. In instruction and evaluation, the inordinately heavy emphasis on factual content needs supplementation with the sponsoring of creative, integrated thinking and with discussions on the historical and philosophical aspects of medicine as a component of modern science, instead of considering it merely as a utilitarian task, that would produce only medical technicians, and not medical scientists, whom our country needs.